Psychiatric profile of motor subtypes of de novo drug‐naïve Parkinson's disease patients. Issue 10 (30th August 2018) - Assogna, Francesca; Pellicano, Clelia; Cravello, Luca; Savini, Cinzia; Pierantozzi, Mariangela; Mercuri, Bruno; Caltagirone, Carlo; Pontieri, Francesco E.; Spalletta, Gianfranco; Stefani, Alessandro
Abstract: Background: Parkinson's disease (PD) is a heterogeneous neurodegenerative disorder. It is well established that different motor subtypes of PD evolve with different clinical courses and prognoses. The complete psychiatric profile underlying these different phenotypes since the very early stage of the disease is debated. Aims of the study: We aimed at investigating the psychiatric profile of the three motor subtypes of PD (akinetic‐rigid, tremor‐dominant, and mixed) in de novo drug‐naïve patients with PD. Methods: Sixty‐eight patients with PD, divided into 39 akinetic‐rigid (AR), seven mixed (MIX), and 22 tremor‐dominant (TD) patients underwent a complete assessment of psychiatric, cognitive, and motor symptoms. Results: No significant differences were found among groups. Conclusions: Our results suggest that a differentiation of the psychiatric symptoms associated with specific motor subtypes of PD is not detectable in de novo drug‐naïve patients. Previous evidence that emerges later along the disease progression may be a consequence of the dopaminergic and nondopaminergic damage increase. Abstract : It is well established that different motor subtypes of PD evolve with different clinical courses and prognoses. Here, we investigated psychiatric profile of three motor subtypes of PD (akinetic‐rigid, tremor‐dominant, and mixed) in newly diagnosed drug naïve patients with PD. A differentiation on the non‐motor symptoms associated with specific motor subtypes of PD is not detectable in newly diagnosed drug naïve patients; therefore, it emerges later along the disease progression.